Experrimental Research on Lubricants for Double Enveloping Wormgearing Generated from Planar Surface - 孟惠荣; 连香姣; 范迅; 唐劲松; 朱和令; 张德华; 靳建民; 王领娣 (Jixie chuandong)
A exDrimental research has been done on 6 domestic wormgear lubricants for double enveloping wormgearing generated from planar surface.Test results and comments covering efficiencies,temperature rises,and maximam thermal load capacities were to develope a new generation of wormgear lubricants.